PENGARUH PENUNDAAN PEMERIKSAAN SPESIMEN URINE DENGAN PENYIMPANAN PADA COOLBOX TERHADAP VIABILITAS BAKTERI - Ni Wayan Desi Bintari; Nyoman Sudarma (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
The natural course of the disease in patients with urinary tract infections (UTIs) is often unpredictable, so a proper diagnosis is needed through accurate laboratory tests. Urine specimen management is important for laboratory staff to pay attention to because delays in examination risk increasing false positive or negative results. The purpose of this study was to determine whether there was an effect of delaying the examination of urine specimens stored in a cool box on the viability of bacteria from urine culture examination results. The type of research was experimental, conducted at the Bacteriology Laboratory of STIKES Wira Medika Bali in June-August 2024. The experimental group consisted of delays in urine specimen examination for 0 hours, 2 hours, 4 hours and 6 hours. The calculation of bacterial viability was carried out by examining urine cultures with a calibrated loop technique. The research data were analyzed using the Kruskal Wallis bivariate test. The results showed that there was no significant difference in the viability of bacteria from urine culture at delays of 0 hours, 2 hours, 4 hours and 6 hours (p> 0.05) stored in a cool box. Urine specimens for calculating bacterial viability were still stable in cool box storage up to a delay time of 6 hours. It is suggested that further research is needed to determine whether there is a difference in bacterial viability in specimens stored in a cool box with a delay time of > 6 hours.